MK2 Regulates Macrophage Chemokine Activity and Recruitment to Promote Colon Tumor Growth - Phinney, Brandon B.; Ray, Anita L.; Peretti, Amanda S.; Jerman, Stephanie J.; Grim, Carl; Pinchuk, Irina V.; Beswick, Ellen J. (Frontiers in Immunology, 2018)
A major risk factor for colon cancer growth and progression is chronic inflammation. We have shown that the MAPK-activated protein kinase 2 (MK2) pathway is critical for colon tumor growth in colitis-associated and spontaneous colon cancer models. This pathway is known to regulate expression of the tumor-promoting cytokines, IL-1, IL-6, and TNF-α. However, little is known about the ability of MK2 to regulate chemokine production. This is the first study to demonstrate this pathway also regulates the chemokines, MCP-1, Mip-1α, and Mip-2α. We show that these chemokines induce tumor cell growth and invasion in vitro and that MK2 inhibition suppresses tumor cell production of chemokines and reverses these pro-tumorigenic effects. Addition of MCP-1, Mip-1α, and Mip-2α to colon tumors in vivo significantly enhanced tumor growth in control tumors and restored tumor growth in the presence of MK2 inhibition. We also demonstrate that MK2 signaling is critical for chemokine expression and macrophage influx to the colon tumor microenvironment. MK2 signaling in macrophages was essential for inflammatory cytokine/chemokine production, whereas MK2-/- macrophages or MK2 inhibitor treatment suppressed cytokine expression. We show that addition of bone marrow-derived macrophages to the tumor microenvironment enhanced tumor growth in control tumors and restored tumor growth in tumors treated with MK2 inhibitors, while addition of MK2-/- macrophages had no effect. This is the first study to demonstrate the critical role of the MK2 pathway in chemokine production, macrophage influx, macrophage function, and tumor growth.